Constructal design of T-shaped morphing fins coupled with a trapezoidal basement: A numerical investigation by means of exhaustive search and genetic algorithm. (June 2017) - Biserni, C.; Dalpiaz, F.L.; Fagundes, T.M.; Rocha, L.A.O.
Highlights: Constructal design is used associated with exhaustive search and genetic algorithm. The best shapes emerge when the geometry has freedom to morph. All the best configurations are the ones that distribute better the hot spots. Abstract: In the present work constructal design is employed to optimize the geometry of morphing T-shaped fins that remove a constant heat generation rate from a trapezoidal basement. The fins are bathed by a steady stream with constant ambient temperature and convective heat transfer. The trapezoidal body that serves as a basement for the T-shaped construct generates thermal energy uniformly and it is perfectly insulated on the outer perimeter. It is shown numerically that the global thermal resistance of the T-shaped construct can be minimized by geometric optimization subjected to constraints, namely, the basement area constraint, the T-shaped fins area fraction constraint and the auxiliary area fraction constraint, i.e. the ratio between the area that circumscribes the T-shaped fin and the basement area. The combination of the degrees of freedom values in the context of constructal design generated a search space with several "potential" local minima so that the classic technique, i.e. the exhaustive search, had to be substituted by the genetic algorithm method. First achieved results indicate that when the geometry is free to morph then the thermal performance is improved according to the constructal principle named by Bejan "optimal distribution of imperfections".